Survey of the Implementation of Traditional Games of Minangkabau in Physical Education in Elementary School - Meiriani Armen; Apriyanti Rahmalia; Yulfia Nora; M. Iqbal Tuwanta Salamaka (STKIP Muhammadiyah Kuningan, 2022)
The background of this research is that several teachers in elementary schools throughout the Nanggalo sub-district still have not implemented traditional Minangkabau games in physical education learning. The purpose of this study was to determine the extent of the application of traditional Minangkabau games in Physical Education knowledge in 2019-2020. The research method is a survey method with an instrument in the form of a research questionnaire in the form of a google form (online), with the research subjects being Physical Education teachers from elementary schools throughout the Nanggalo Padang sub-district, totaling 27 elementary schools with a total of 29 PJOK teachers. The data analysis technique used descriptive analysis in the form of percentages. The results of the study on the survey of the application of traditional Minangkabau games in physical education learning in elementary schools throughout the Nanggalo district of Padang city were seen from the number of elementary schools with a percentage of 74% public elementary schools, 19% private elementary schools and private elementary schools that did not have PJOK teachers 7%. Judging from the number of teachers with 62% male teachers and 38% female teachers. For the results of the application of traditional Minangkabau games in physical education learning with a percentage of 50.10% in the category of applying and 49.90% of the type not using. It can be concluded that PJOK teachers have implemented traditional Minangkabau games.